Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Aljabar Ditinjau Dari Taksonomi Solo Pada Siswa Kelas Vii SMP Negeri 1 Sambi Tahun Ajaran 2015/2016 - Puspitasari, Nandya (2016)
Mathematics is one important part of science. Studying mathematics is useful for the development of competence and as a means of systematic thinking, logical, creative and consistent. Scale international assessment PISA, suggesting that mathematics achievement in Indonesia is still far behind from other countries. The low math achievement is inseparable from the learning process in schools. Errors students need to be analyzed in detail in order errors and the causes may soon be known so that it can be minimized and the solution may be given a solution. This study aimed to describe the mistakes made in doing algebra students were evaluated from five levels SOLO taxonomy. This research is a qualitative descriptive. The subjects were students of class VII A SMP Negeri 1 Sambi totaling 32 students. The data collection technique using the test method, interviews, observation and documentation. Data validation was done by triangulation of data sources by comparing the results of the test method, interviews, observation and documentation. Data analysis technique conducted in stages, data reduction, data presentation, verification and conclusion. The results were obtained on a five-level error SOLO taxonomy with a large percentage of which prestructural level of 32.03%, 42.18% unistructural level, multistructural level of 14.06%, 6.25% relational level, and extended abstract level of 5.46%. The results indicate students errors at the level unistructural more dominant than the other level with the type of error the concept and principles of the error type. Error student at unistructural level due to the low ability students in interpreting the data, weak memory of students, the attitude of haste students work on the problems, the weak students in understanding the concept of substitution methods and weak ability of students to translate problems into mathematical models.